2007
DOI: 10.1002/ibd.20061
|View full text |Cite
|
Sign up to set email alerts
|

Group-based intervention program in inflammatory bowel disease patients

Abstract: The group-based intervention program was feasible and highly appreciated. There were no statistically significant differences in average IBDQ or SOC over time or in comparison with controls, although a significant increase was seen in patients with short disease duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 27 publications
6
65
0
1
Order By: Relevance
“…27,28,81,139 The studies incorporated a broad range of treatments (e.g., psychodynamic therapy, supportive therapy, and cognitive behavioral therapies), some of which are not as well supported empirically, and often involved unselected IBD patients or those in remission with little elevated distress, 134,140 resulting in the potential for floor effects. As such, the conclusion to date is not surprising, and…”
Section: Psychological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28,81,139 The studies incorporated a broad range of treatments (e.g., psychodynamic therapy, supportive therapy, and cognitive behavioral therapies), some of which are not as well supported empirically, and often involved unselected IBD patients or those in remission with little elevated distress, 134,140 resulting in the potential for floor effects. As such, the conclusion to date is not surprising, and…”
Section: Psychological Treatmentmentioning
confidence: 99%
“…142 Other indicators of receptivity included positive evaluations of treatment 140 and low drop out rates, despite the expectation of active participation. 134,137 In conclusion, effective psychological treatments are available for anxiety and depression.…”
Section: 139mentioning
confidence: 99%
“…These studies incorporated a broad range of treatments (e.g., psychodynamic therapy, supportive therapy, and cognitive behavioral therapies), some of which are not as well supported empirically. Further, the studies often involved unselected IBD patients or patients in remission with little elevated distress [112,113] , resulting in the potential for floor effects. Thus, unsurprisingly, psychological treatment is not indicated for all patients with IBD [114] .…”
Section: Psychotherapeutic Approachmentioning
confidence: 99%
“…A structured measure of desire for psychological care comparing patients with IBD and rheumatoid arthritis found that 2 to 3 times the number of IBD patients (31%) expressed an interest in receiving assistance compared to individuals with rheumatoid arthritis (13%) [116] . Other indicators of receptivity included positive evaluations of treatment [113] and low dropout rates despite the expectation of active participation [104,106] .…”
Section: Psychotherapeutic Approachmentioning
confidence: 99%
“…Another treatment consisting of 10 weekly two hour group sessions covering psycho education, relaxation, problem solving techniques, social skill training, and cognitive restructuring, significantly improved emotional functioning, including anxiety and depression, in IBD patients compared to waitlist controls for up to 12 months post treatment [31]. However, nine weekly sessions of alternating group therapy with lectures on psycho education, did not significantly improve HRQoL or coping ability at 6 or 12 months post treatment in 24 IBD patients compared to 20 controls [62]. Interestingly, patients with 3 years or less of disease duration did show improvement on both coping and HRQoL.…”
Section: Group Therapymentioning
confidence: 99%